Critical Analysis of J.M.S. Baljon's Perspectives in Tafsir Study - Irwanto; Katimin, Rudiyanto; Usiandra, Teuku Erdika (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
J.M.S. Baljon's ideas in the study of Quranic interpretation provide significant contributions through the historical-critical approach it employs. As an orientalist, Baljon explored the historical context of revelation and challenged the traditional interpretations that have long dominated the Islamic world. This approach opens up space to understand the Quran from a broader and more dynamic perspective, which not only considers theological aspects but also historical and sociological dimensions. This research is a narrative study about Baljon J.M.S and his thoughts. This research uses qualitative narrative study through the analysis of books and articles that contain information about Baljon. This analysis demonstrates how Baljon uses critical methods to assess the authenticity and relevance of traditional interpretations in a modern context. However, Baljon's approach has faced criticism, particularly regarding the use of Western assumptions that are considered less relevant to Islamic tradition. These criticisms include concerns about the potential bias and generalization that might overlook the complexity of interpreting the Qur'an. Nevertheless, Baljon's ideas remain relevant in fostering dialogue between Islamic tradition and Orientalist studies, as well as enriching the discourse of exegesis with critical perspectives that can deepen the understanding of sacred texts in contemporary contexts.